Analysis of Glucosinolate Content and Metabolism Related Genes in Different Parts of Chinese Flowering Cabbage - Feng, Xianjun; Ma, Jiajun; Liu, Zhiqian; Li, Xuan; Wu, Yinghua; Hou, Leiping; Li, Meilan (Frontiers in Plant Science, 2022)
Glucosinolates (GSLs) are important secondary metabolites that play important defensive roles in cruciferous plants. Chinese flowering cabbage, one of the most common vegetable crops, is rich in GSLs and thus has the potential to reduce the risk of cancer in humans. Many genes that are involved in GSL biosynthesis and metabolism have been identified in the model plant Arabidopsis thaliana; however, few studies investigated the genes related to GSL biosynthesis and metabolism in Chinese flowering cabbage. In the present study, the GSL composition and content in three different organs of Chinese flowering cabbage (leaf, stalk, and flower bud) were determined. Our results showed that the total GSL content in flower buds was significantly higher than in stalks and leaves, and aliphatic GSLs were the most abundant GSL type. To understand the molecular mechanisms underlying the variations of GSL content, we analyzed the expression of genes encoding enzymes involved in GSL biosynthesis and transport in different tissues of Chinese flowering cabbage using RNA sequencing; the expression levels of most genes were found to be consistent with the pattern of total GSL content. Correlation and consistency analysis of differentially expressed genes from different organs with the GSL content revealed that seven genes (Bra029966, Bra012640, Bra016787, Bra011761, Bra006830, Bra011759 and Bra029248) were positively correlated with GSL content. These findings provide a molecular basis for further elucidating GSL biosynthesis and transport in Chinese flowering cabbage.